Spatial configuration, building microclimate and thermal comfort: A modern house case - Du, Xiaoyu (A+BE | Architecture and the Built Environment, 2019)
In this paper, the authors attempt to clarify the relationship between spatial configuration, building microclimate and thermal comfort through the investigation of a modern house in hot and humid climate with spatial diversity. First, the spatial configuration of the house was analysed in detail. The spatial geometric features, spatial boundary conditions, and human activities in the building were categorised. Secondly, field measurements were conducted to investigate the microclimate of the house. The air temperature, relative humidity and wind velocity were monitored on typical summer days. Thirdly, a dynamic thermal simulation was performed to predict the thermal comfort performance of the building over the period of an entire summer. The simulated results were compared with the measurements, and the adaptive thermal comfort approach was used to evaluate the thermal comfort. The modern house studied was found to have a varied spatial configuration, similar to local vernacular buildings, which produces diverse thermal environments in the building. The microclimate of this specific building could provide considerable thermal comfort for the occupants in summer under the local climate conditions, although thermal comfort cannot be achieved through free-running model in the hottest days, mechanical cooling or mixed model are needed.